2003
DOI: 10.1111/1540-5907.00012
|View full text |Cite
|
Sign up to set email alerts
|

Are Patriots Bigots? An Inquiry into the Vices of In‐Group Pride

Abstract: One view in the study of intergroup conflict is that pride implies prejudice. However, an increasing number of scholars have come to view in-group pride more benignly, suggesting that such pride can be accompanied by a full range of feelings toward the out-group. In this article, we focus on a substantively interesting case of in-group/out-group attitudes-national pride and hostility toward immigrants. We explore the relationship in two fundamental ways: first by examining the prejudice associated with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
272
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(294 citation statements)
references
References 32 publications
13
272
2
7
Order By: Relevance
“…This statistic is evaluated against the chi-square distribution, with a degrees of freedom equal to the number of variables included in the variance equation for the full model. 6 Nevertheless, in a somewhat different context, analyses by de Figueiredo and Elkins (2003) using a variant of two-stage least-squares regression deal somewhat with the possibility of reciprocal effects by correcting for the effects of simultaneity in the prediction of policy attitudes from nationalism and patriotism. More specifically, they found that the relationship between nationalism and attitudes toward immigrants -and the lack of a relationship between patriotism and this dependent variable -was robust to functional forms which corrected for the relationship between these two predictors and the residual variance in attitudes toward immigrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This statistic is evaluated against the chi-square distribution, with a degrees of freedom equal to the number of variables included in the variance equation for the full model. 6 Nevertheless, in a somewhat different context, analyses by de Figueiredo and Elkins (2003) using a variant of two-stage least-squares regression deal somewhat with the possibility of reciprocal effects by correcting for the effects of simultaneity in the prediction of policy attitudes from nationalism and patriotism. More specifically, they found that the relationship between nationalism and attitudes toward immigrants -and the lack of a relationship between patriotism and this dependent variable -was robust to functional forms which corrected for the relationship between these two predictors and the residual variance in attitudes toward immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing research also suggests that identification with the national ingroup may not be a unitary dimension. More precisely, a variety of studies have distinguished between national attachment in the form of patriotism and national Need for closure and attitudes toward Iraq -7 attachment in the form of nationalism (de Figueiredo & Elkins, 2003;Dekker, Malova, and Hoogendoorn, 2003;Feshbach, 1994;Kosterman & Feshbach, 1989;Sidanius et al, 1997;Viroli, 1995). So, what are the basic elements of this distinction?…”
Section: Need For Cognitive Closure and Intergroup Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wanneer etniese groeperinge as probleemmense gesien word, soos in Nederland (De Figueiredo & Elkins, 2003;Perkins, 2003;Smelink, 1999), vind stereotipering plaas, omdat veralgemeen word en omdat 'probleem' 'n negatiewe assosiasie het. Terselfdertyd is dit eufemisties omdat dit nie openlik vyandig is nie.…”
Section: Nederlandunclassified
“…Researchers, however, commonly agree that a key dimension of these processes involves external threat and foreign intervention. 2 Nationalist awareness and pride are particularly provoked under direct foreign domination when the indigenous people feel that they were being, in Gellner's words, "bossed and knocked about by others with whom they cannot or are not allowed to identify" (cited in O'Leary 1997: 196;see also Hobsbawm 1990;Mueller 1973;Centlivres and Centlivres-Demont 2000;de Figueiredo and Elkins 2003;Davis and Silver 2004). 3 The key question is thus not whether foreign occupation affects national pride.…”
Section: Foreign Occupation and National Pridementioning
confidence: 99%